DeFi Lending : Beyond the Hype - Balogh, Karel (2022)
With an aggregate liquidity supply of more than $45 billion, decentralized lending protocols are gaining traction as an important component of the decentralized finance (DeFi) ecosystem. In this thesis, I analyze the constraints of conventional money markets dominated by banks and lending platforms, as well as the benefits of DeFi lending protocols for tackling entrenched inefficiencies in the current lending environment. Using the case studies of Anchor, Maker, Aave, and Compound, this thesis explores the mechanics of DeFi lending systems. I investigate DeFi lending's ongoing reliance on the current financial system, as well as its exploits, prospective innovations, and risks, before concluding with a market summary, future projection, and potential future research areas via using Twitter data.